Avaliação de diferentes meios de armazenagem para dentes avulsionados: estudo experimental em cães - Reis, Manuella Verdinelli de Paula (2013)
Studies have proposed coconut water, and more recently soy milk as storage medium for avulsed teeth, due to their nutrients are important factors to nutrition and preservation of cell viability. This study investigated the ability of pH-adjusted coconut water and soy milk to maintain the viability of periodontal ligament cells compared with bovine whole milk, bovine skim milk, and Hank s Balanced Salt Solution by using trypan blue exclusion; and the periodontal healing process of dog teeth replanted after storage in these solutions by using µCT and histological analyses compared with immediately tooth replantation. The solutions were evaluated by percentage of viable cells. For in vitro study were extracted dog premolar teeth, dried for 30 min on the surface of a gauze, and stored in the following media for 50 min or 24 h: long shelf-life bovine whole milk (SWM) (n=8), long shelf-life skim milk (SSM) (n=8), Hank s Balanced Salt Solution (HBSS) (n=8), soy milk (SM) (n=8) and pH-adjusted coconut water (CW) (n=8). The positive and two negative control groups corresponded to 0-min, 30-min (short-term), and 24-h (long-term) dry times, respectively. For in vivo study, forty upper and lower incisors of 10 adult beagle dogs were extracted and subjected to the following protocols: immediate replantation after extraction (control) (n=10); stored immediately in coconut water with adjusted pH (CW) (n=9), soy milk (SM) (n=8) and bovine whole milk (WM) (n=9), respectively for 50 minutes before replantation. The animals were euthanized 28 days postoperatively and the specimens obtained were scanned by µCT and subjected to routine processing for histometric analyses under optical microscope. The results obtained in vitro for the short-term experiment, the SSM resulted in significantly lower cell viability than SM and CW. At 24 h, SM and CW resulted in higher viability than HBSS and SSM and in comparable performance with the positive control group (0 min). Cell viability decreased over time (24 h), except in SM and CW. In vivo study showed that CW and SM had a similar periodontal condition performance of WM; however CW demonstrated lower variability of the periodontal condition than SM. SM demonstrated significant higher ankylosis than control group. Additionally this study demonstrated that the association of µCT and histological analyses for in vivo study is a promise method to better clarify the different stages of the tissue repairs. A despite of the results obtained in vitro, the in vivo study presented CW as superior storage media for avulsed teeth.